2019
DOI: 10.18203/2320-6012.ijrms20194320
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in adult Nigerians: patients’ characteristics, laboratory profile, practices and management outcome

Abstract: Background: Type 2 diabetes constitutes more than 90% of cases seen in Nigeria. Previous reports had shown that patients were poorly controlled and failed to meet management target across a broad range of parameters. Objectives of this study evaluated the characteristics and practices of patients attending the outpatient diabetes clinic. The study also examined to what extent they achieved management goals and what practices by the patients impacted negatively on treatment outcome.Methods: This was a cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Furthermore, it was also noted that some older studies conducted in Nigeria reported lower prevalence of hypertension (25% to 54.2%) (Osuntokun et al, 1972;Okesina et al, 1995;Chuhwak et al, 2002;Unadike et al, 2011;Odeyinka and Ajayi, 2017), but not less than 30% occurrence of dyslipidaemia and obesity (Awosan et al, 2013). But in agreement with our findings, more recent studies in the country have shown higher proportions of hypertension (74% and 85.5%) and obesity (60% and 51.2%) in patients with T2DM (Onyenekwe et al, 2019;David et al, 2019). This steady increase in cardiovascular risk factors among diabetic population in Nigeria from 25% in 1972 (Osuntokun et al, 1972) to 85.5% in 2019 (David et al, 2019) may be related to westernised lifestyle, nutrition transition, rapid urbanization, increased sedentary lifestyle, physical inactivity, ageing population and poor glycaemic control (Hu et al, 2011;ADA, 2022).…”
Section: Cardiovascular Risk Factorssupporting
confidence: 93%
“…Furthermore, it was also noted that some older studies conducted in Nigeria reported lower prevalence of hypertension (25% to 54.2%) (Osuntokun et al, 1972;Okesina et al, 1995;Chuhwak et al, 2002;Unadike et al, 2011;Odeyinka and Ajayi, 2017), but not less than 30% occurrence of dyslipidaemia and obesity (Awosan et al, 2013). But in agreement with our findings, more recent studies in the country have shown higher proportions of hypertension (74% and 85.5%) and obesity (60% and 51.2%) in patients with T2DM (Onyenekwe et al, 2019;David et al, 2019). This steady increase in cardiovascular risk factors among diabetic population in Nigeria from 25% in 1972 (Osuntokun et al, 1972) to 85.5% in 2019 (David et al, 2019) may be related to westernised lifestyle, nutrition transition, rapid urbanization, increased sedentary lifestyle, physical inactivity, ageing population and poor glycaemic control (Hu et al, 2011;ADA, 2022).…”
Section: Cardiovascular Risk Factorssupporting
confidence: 93%
“…The cardiovascular system in particular accounts for about 75% of hospitalizations and mortality from complications of diabetes in diabetics. Diabetes tends to cluster with other CVD risk factors particularly HTN which occurs in 50-70% of diabetics and is known [1][2][3][4][5][12][13][14][15] to worsen pathological changes in the end organs. This study set out to determine the left ventricular geometry and function in normotensive and hypertensive type 2 diabetics without overt cardiac symptoms and associated factors.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetic heart disease is a spectrum that involves a progression from the normal heart to preclinical cardiac dysfunction (detectable by echocardiography), symptomatic cardiac dysfunction [6][7][8][9][10][11] and finally congestive cardiac failure. Hypertension which occurs in about 50-70% of patients with T2DM is [1][2][3][4][5][12][13][14][15] known to accelerate and worsen these changes. Studies have been ambivalent with regards to LV geometry/function in normotensive/hypertensive [16][17][18][19][20] T2DM patients without cardiac symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Skipping medication in effort to prevent hypoglycaemia, which is said to occur more in men, has been pointed out to play a major role in under-management of diabetes. This study was therefore set up to investigate these claims and determine which gender has DM undermanaged, and requiring more attention among diabetic patients in Sabon Gari LGA of Kaduna State, Nigeria, and a probable reason why it is so [4][5][6].…”
Section: Introductionmentioning
confidence: 99%